The dynamics of economic integration: Theory and policy - Lucas Bretschger; Thomas M. Steger (ETH Zurich, CER-ETH - Center of Economic Research, 2004)
Integration a.ects economic growth mainly through two different channels : The scale-effect channel and the factor-reallocation channel. In order to investigate both channels within a unifying framework, we employ a simple descriptive growth model. The scale-effect channel increases either the long-run growth rate or the level of the balanced growth path. The factor-reallocation channel is ambiguous. It is shown under which conditions this mechanism induces either a rise or a fall in the long-run growth rate. In addition, a number of policy conclusions are drawn.
Keywords: F1; O4; 330; trade; economic integration; economic growth; scale effects; factor reallocation; Wirtschaftsintegration; Wirtschaftsintegration; Allokation; Handelseffekt; Wirtschaftswachstum; Theorie